Model Oriented Approach for Industrial Software Development - P. D. Drobintsev; V. P. Kotlyarov; N. V. Voinov; I. V. Nikiforov (Моделирование и анализ информационных систем, 2015)
The article considers the specifics of a model oriented approach to software development based on the usage of Model Driven Architecture (MDA), Model Driven Software Development (MDSD) and Model Driven Development (MDD) technologies. Benefits of this approach usage in the software development industry are described. The main emphasis is put on the system design, automated code generation for large systems, verification, proof of system properties and reduction of bug density. Drawbacks of the approach are also considered. The approach proposed in the article is specific for industrial software systems development. These systems are characterized by different levels of abstraction, which is used on modeling and code development phases. The approach allows to detail the model to the level of the system code, at the same time store the verified model semantics and provide the checking of the whole detailed model. Steps of translating abstract data structures (including transactions, signals and their parameters) into data structures used in detailed system implementation are presented. Also the grammar of a language for specifying rules of abstract model data structures transformation into real system detailed data structures is described. The results of applying the proposed method in the industrial technology are shown.The article is published in the authors’ wording.